International control over family law provisions: Matrimonial custody as a model - Aidaoui, Chemseddine; Mahrouk, Karima (Journal of Human Sciences, 2022)
The laws of the Arab family have become a focus of great international attention, after the ratification of many human rights charters in general and women's rights charters in particular with the existence of many provisions based on gender inequality in these laws, such as marital correctness.These countries are required to amend and harmonize their laws with the provisions of the conventions, based on the supremacy of the treaty over the law.